A characterization of minimal ascreen null hypersurfaces of $(LCS)$-space forms - Ssekajja, Samuel (My University, 2019)
In the present paper, we study non totally geodesic minimal ascreen null hypersurface, M, of a Lorentzian concircular structure (LCS)-space form of constant curvature 0 or 1. We prove that; if the Ricci tensor of M is parallel with respect to any leaf of its screen distribution, then M is isometric to a product of a null curve and spheres.
Keywords: Lorentzian concircular structures; Minimal hypersurfaces; Null hypersurfaces